HUBUNGAN KOMUNIKASI TIM BEDAH TERHADAP KEPATUHAN PENERAPAN SURGICAL SAFETY CHEKLIST DI RSUD DR H M RABAIN MUARA ENIM - Martin, Weddy; Bilqis, Ranne; Untari, Puthi Dwi (Universitas Sumatera Barat, 2024)
Background: one of the most important aspects of patient safety is communication, where communication is an exchange of thoughts, feelings and opinions that occurs between two or more people who work together regarding an action or work. The aim of this study was to determine the relationship between surgical team communication and compliance with the implementation of the surgical safety checklist. Analytical survey research design with a cross sectional approach. Population and sample using total sampling with a total of 30 respondents. Data analysis used univariate analysis and bivariate analysis using the chi square test. Results of the research showed that 27 respondents (90%) communicated well with the surgical team and 3 respondents (10%) did not, 27 respondents (90%) complied with implementing the Surgical Safety Checklist and 3 respondents (10%) did not comply. implement the Surgical Safety Checklist. The results of the Shi square test obtained a p value = 0.020. Conclusion is that there is a significant relationship between surgical team communication and compliance with the implementation of the Surgical Safety Checklist at Dr H M Rabain Muara Enim Regional General Hospital (RSUD). Suggestion: it is hoped that it can be used as evaluation material for hospitals to be able to improve the quality of service and always comply with all procedures within the scope of the hospital